Klimt landscapes - Staggs, Janis; Digney-Peer, Shawn; Faber, Monika 1954-; Pallestrang, Kathrin 1971-; Yass-Alston, Yagna (Prestel, 2024)
As inviting and sensual as a warm summer day, this opulent exhibition catalog offers a deep appreciation of Klimt’s ornate, exquisitely detailed, and atmospheric landscape paintings. For the last twenty years of his career, Gustav Klimt devoted considerable energy to painting landscapes during his summer vacations—and these bucolic scenes became some of his most sought-after pictures. Filled with vibrant high-quality reproductions and featuring engaging essays by leading scholars in the field, this exhibition catalog situates Klimt’s landscapes alongside fin-de-siècle fashion, photography, and decorative arts of the Wiener Werkstätte in particular. Klimt’s landscapes are examined within the context of his larger oeuvre and traces the evolution of his style: from one informed by the academic tradition, to his ornate "golden style" decorative approach influenced by the ideal of the Gesamtkunstwerk, and then to a more painterly manner of working in pure color. The book also considers Klimt’s relationship with his muse, fashion designer Emilie Flöge; his deep engagement with the Viennese avant-garde; and the specific techniques he employed to achieve mesmerizing, harmonious works that literally shimmer with light and color
Rückseite Titelblatt: This catalogue has been published in conjunction with the exhibition "Klimt Landscapes", Neue Galerie New York, February 15, 2024 - May 6, 2024
Keywords: Klimt, Gustav -- 1862-1918; Landschaftsmalerei; Ausstellungskatalog -- Neue Galerie New York -- 15.02.2024-06.05.2024 -- New York, NY